NonO Is a Novel Co-factor of PRDM1 and Regulates Inflammatory Response in Monocyte Derived-Dendritic Cells - Kyungwoo Lee; Su Hwa Jang; Su Hwa Jang; Hong Tian; Sun Jung Kim (Frontiers in Immunology, 2020)
Proper expression of the transcription factor, Positive regulatory domain 1 (PRDM1), is required for maintaining homeostasis of human monocyte derived-dendritic cells (MO-DCs). The molecular mechanisms and gene targets of PRDM1 in B and T lymphocytes have been identified. However, the function of PRDM1 in dendritic cells (DCs) remains unclear. We investigate co-regulators of PRDM1 in MO-DCs identified by mass spectrometry (MS) and co-immunoprecipitation (Co-IP). Notably, non-POU domain-containing octamer-binding protein (NonO) was found to be a PRDM1 binding protein in the nucleus of MO-DCs. NonO is recruited to the PRDM1 binding site in the promoter region of IL-6. Knockdown of NonO expression by siRNA lessened suppression of IL-6 promoter activity by PRMD1 following LPS stimulation. While NonO binding to PRDM1 was observed in human myeloma cell lines, an effect of NonO on IL-6 expression was not observed. Thus, loss of NonO interrupted the inhibitory effect of PRDM1 on IL-6 expression in MO-DCs, but not plasma cells. Moreover, MO-DCs with low expression of PRDM1 or NonO induce an increased number of IL-21-producing TFH-like cells in vitro. These data suggest that low level of PRDM1 and NonO lead to enhanced activation of MO-DCs and the regulation of MO-DC function by PRDM1 is mediated through cell lineage-specific mechanisms.